Folding and design of helical repeat proteins - Regan, Lynne (Henry Stewart Talks, 2007)
Repeat proteins versus globular proteins, Consensus design, the role of conserved hydrophobic residues, Co-variation can modulate stability, but is not essential to specify a stable fold, Structure and stability of the designed CTPR proteins, The thermodynamic behavior of repeat proteins in terms of a 1D Ising model, Amide H-exchange to study stability on a residue specific basis, The structure of long TPRs, Hypervariability defines the ligand binding site: a general result, Functional TPR designs, Useful designer proteins, The awesome power of screens and selections
Reviewed at 2015/08/24